Blumhouse productions : the new house of horror - Platts, Todd K.; McCollum, Victoria; Clasen, Mathias F. (Cardiff : University of Wales Press, 2022)
"Blumhouse Productions: The New House of Horror provides the first sustained academic inquiry into one of the biggest production companies currently working in horror film production. Scholars from a wide range of disciplines explore various facets of the company, which is known for such hit franchises as Paranormal Activity, Insidious, and The Purge, in addition to critically acclaimed works such as Get Out, and box office sensations such as Happy Death Day and Split. Balancing attention to the behind-the-scenes workings of the company and its productions with accounts of the films themselves, the book presents a thorough and detailed picture of Blumhouse Productions and its cultural footprint."--Publisher description.
Introduction / Victoria McCollum, Mathias Clasen and Todd K. Platts -- Blumhouse at the box office, 2009-2018 / Todd K. Platts -- 'Those things you see through' : Get out, Signifyin', and Hollywood's commodification of African-American independent cinema / Stefan Sereda -- Haunted bodies, haunted houses / Racheal Harris -- Gothixity : evoking the Gothic through new forms of toxic masculinity / Fernando Gabriel Pagnoni Berns -- Space invaders : aliens and recessionary anxieties in Dark skies / Craig Ian Mann -- The (Blum)house that found-footage horror built / Shellie McMurdo -- Insidious patterns : an integrative analysis of Blumhouse's most important franchise / Todd K. Platts, Victoria McCollum and Mathias Clasen -- The purge : violence and religion, a toxic cocktail / Amanda Rutherford and Sarah Baker -- Happy death day : beyond the neo-slasher cycle / Sotiris Petridis -- Haunted networks : transparency and exposure in Unfriended and Unfriended : dark web / Zak Bronson -- Shifting shapes : Blumhouse's Halloween (2018) and the new ethos of slasher remakes / Guy Spriggs -- 'Disobedient women' and malicious men : a comparative assessment of the politics of Black Christmas (1974) and (2019) / John Kavanagh -- What lies behind the white hood : looking at horror through a realistic lens in Spike Lee's BlacKkKlansman / Allison Schottenstein.
Includes bibliographical references (pages 255-278) and index.
Online resource; title from pdf information screen (EBSCO, viewed November 8, 2023)
eBooks on EBSCOhost
Keywords: Blumhouse Productions; Horror films -- Production and direction; Films d'horreur -- Production et réalisation.; Horror films -- Production and direction; FICTION / Horror